FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN ANTENATAL CARE (ANC) PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS LUBUK BUAYA KOTA PADANG - Rafika Oktova; Erda Mutiara Halida; Yeri Englania Rusmat (Midwifery Department of Health Polytechnic, Ministry of Health, Denpasar, 2023)
The Maternal Mortality Rate (MMR) in Indonesia in 2021 is 7,389 cases, which shows an increase compared to 2020. The high maternal mortality rate (MMR) in Indonesia is related to many factors, including the quality of behavior of pregnant women who do not use antenatal care in pregnancy health services. This study aims to determine the relationship between these factors and antenatal care visits (ANC) in the Lubuk Buaya Health Center, Padang City, working area. This type of research used quantitative research with a cross-sectional study design; the sample in this study were all postpartum mothers who were in the Working Area of the Lubuk Buaya Health Center, Padang City, totaling 82 people. The sampling technique in this study is total sampling. Data were obtained from questionnaires filled out by respondents and analyzed using the chi-square statistical test (p≤0.05). The results showed that most of the respondents had complete antenatal care visits, were not at risk of age, had good knowledge, a good attitude, did not work, and had support from their families. The results of the bivariate analysis showed that there was a significant relationship between age (p=0.003), knowledge (p=0.049), attitude (p=0.039), employment (p=0.000), family support (p=0.002), and antenatal care visits. There is a relationship between age, knowledge, attitudes, work, family support, and antenatal care visits.